2001
DOI: 10.1289/ehp.01109s2301
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid perturbations as mechanisms for fumonisin carcinogenesis.

Abstract: There is a great deal of evidence that altered sphingolipid metabolism is associated with fumonisin-induced animal diseases including increased apoptotic and oncotic necrosis, and carcinogenesis in rodent liver and kidney. The biochemical consequences of fumonisin disruption of sphingolipid metabolism most likely to alter cell regulation are increased free sphingoid bases and their 1-phosphates, alterations in complex sphingolipids, and decreased ceramide (CER) biosynthesis. Because free sphingoid bases and CE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
105
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(107 citation statements)
references
References 108 publications
0
105
0
2
Order By: Relevance
“…Fumonisin B 1 disrupts sphingolipid metabolism by potently inhibiting the enzyme ceramide synthase (sphinganine Nacetyltransferase) in the de noVo biosynthesis pathway of major sphingolipids, thus causing a rapid increase in free sphinganine (Sa), one of the base precursors (11,12). The levels of free Sa and sphingosine (So) in tissues and biological fluids may be compared by constructing a ratio of Sa to So (Sa/So ratio) that is used as an early biomarker of exposure to the mycotoxin (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fumonisin B 1 disrupts sphingolipid metabolism by potently inhibiting the enzyme ceramide synthase (sphinganine Nacetyltransferase) in the de noVo biosynthesis pathway of major sphingolipids, thus causing a rapid increase in free sphinganine (Sa), one of the base precursors (11,12). The levels of free Sa and sphingosine (So) in tissues and biological fluids may be compared by constructing a ratio of Sa to So (Sa/So ratio) that is used as an early biomarker of exposure to the mycotoxin (13).…”
Section: Introductionmentioning
confidence: 99%
“…The levels of free Sa and sphingosine (So) in tissues and biological fluids may be compared by constructing a ratio of Sa to So (Sa/So ratio) that is used as an early biomarker of exposure to the mycotoxin (13). The inhibition of ceramide synthase is also likely to disrupt overall sphingolipid metabolism and, theoretically, sphingolipidmediated regulation of important cell events such as apoptosis and mitosis, which are probably in part responsible for the cytotoxic and carcinogenic properties of the mycotoxin (11,14).…”
Section: Introductionmentioning
confidence: 99%
“…A more detailed discussion of molecular mechanism is beyond the purpose of this review but can be found elsewhere in this issue (87,(100)(101)(102).…”
Section: Fumonisins and Sphingolipids: Mechanistic Considerationsmentioning
confidence: 99%
“…Many of the fumonisins, particularly of the B series such as fumonisin B 1 (FB 1 ), are potent inhibitors of ceramide synthase. This disruption of sphingolipid metabolism is a major contributor to the toxicity and carcinogenicity of FB 1 , as described in an accompanying review (1). In this present article we summarize information about basic sphingolipidology that may be useful in understanding fumonisin action.…”
mentioning
confidence: 91%
“…Fumonisins are a category of toxic and carcinogeneic mycotoxins that bear a remarkable structural similarity to sphingolipids (1,2). Many of the fumonisins, particularly of the B series such as fumonisin B 1 (FB 1 ), are potent inhibitors of ceramide synthase.…”
mentioning
confidence: 99%